Profile soil organic and inorganic carbon sequestration in maize cropland after long-term straw return - Xie, Mengmeng; Zhang, Tianyu; Liu, Shasha; Liu, Ziping; Wang, Zhongqiang (Frontiers in Environmental Science, 2023)
Promoting cropland carbon (C) sequestration through straw return has always been the focus of numerous studies. However, there is still a lack of comprehensive understanding of the straw return effects on soil organic carbon (SOC) and soil inorganic carbon (SIC) sequestration. Therefore, the present study aims to investigate the effects of long-term straw return on SOC and SIC sequestration across the 0-100 cm soil profile in the maize planting cropland in Northeastern China. The results showed an increasing trend in SOC contents in the 0-100cm soil profile following long-term straw return, while significant decreases in SIC contents were observed in the surface (0-20 cm) and subsoil (20-60 cm) layers, respectively. In addition, the SOC stock increased significantly in the subsoil layer following long-term straw return, by an average value of 44%, which is higher than those observed in other soil layers. On the other hand, the SIC stock in the subsoil layer increased by an average value of 24% and decreased in the surface and under-subsoil layers by average values of 53% and 33%, respectively. Moreover, the exchangeable calcium contents were positively correlated with SOC and SIC stock, demonstrating the soil calcium contributes to SOC and SIC sequestration. The present study highlighted the importance of the subsoil layer for effective straw return strategies in cropland to promote SOC and SIC sequestration in croplands.